"دور الرقمنة في رفع التحصيل الجبائي: دراسة حالة مديرية الضرائب لولاية الوادي " - كمال طواهرية; محمد الحافظ بيكي; البشير زغدي (جامعة الوادي - University of Eloued, 2023)
"تعد الرقمنة من أهم التحولات الحديثة التي يجب أخذها بعين الاعتبار، خاصة بعد الموجة الكبيرة من التطورات التي أحدثتها في الإدارات، خاصة الإدارة الجبائية، حيث ساهمت في تحسين الحصيلة الجبائية والكشف عن التهرب الضريبي بشكل أكثر فعالية ولذلك، كان الهدف الرئيسي لهذه الدراسة هو البحث عن دور الرقمنة في رفع التحصيل الجبائي. تم الاعتماد في هذه الدراسة على المنهج التاريخي والذي يبرز السرد التاريخي لنشأة وتطور الرقمنة، والمنهج الوصفي والذي يتطرق إلى مختلف المفاهيم الخاصة بالموضوع وشرح أبعادها في الجانب النظري من أجل توضيح مفاهيم رقمنه الإدارة الجبائية وتشكيل نظرة علمية حول التحصيل الجبائي، وتم أيضًا استخدام المنهج التحليلي في الجانب التطبيقي، حيث شملت الدراسة مديرية الضرائب بولاية الوادي، كما أنه لغرض جمع المعلومات تم تصميم استبيان وتوزيعه على عينة مكونة من 50 موظف على مستوى مديرية الضرائب لولاية الوادي. ولتحقيق أهداف البحث وتحليل البيانات تم الاعتماد على البرنامج الإحصائي SPSS 25)). وخلصت هذه الدراسة إلى أن موظفي مديرية الضرائب يدركون أهمية ودور الرقمنة في الإدارة الجبائية، وأنها تؤدي إلى زيادة التحصيل الجبائي. وبناءا على هذه النتائج تم تقديم مجموعة اقتراحات من أجل الإسهام في تطبيق رقمنه الإدارة الجبائية ودورها في التحصيل الجبائي. " "Digitization is one of the most important modern transformations that must be taken into account, especially after the large wave of developments it brought about in administrations, mainly tax administration, as it contributed to improving tax revenue and detecting tax evasion more effectively. Therefore, the main objective of this study was to investigate the role of digitization in tax collection. In this study, it was relied on the historical approach, which highlighs the historical narrative of the emergence and devlopment of digitization, and the descriptive approach, which deals with the various concepts of the subject and explains its dimensions in the theoretical aspect in order to clarify the concepts of tax administration digitization and form a scientific view on tax collection. A case study approach was also used on the applied side, as the study included the tax center in El Oued state. Designing a questionnaire and distributing it to a sample of 50 employees at tax diractorate of EL Oued state. To achieve the objectives of the research and data analysis, the statistical program (SPSS 25) was relied upon This study concluded that the employees of the tax center are aware of the importance and role of digitization in tax administration, and that it leads to an increase in tax collection Based on these results, a set of proposals was presented in order to contribute to the application of digitization of tax administration and its role in tax collection. "
Keywords: الإدارة الجبائية، التحصيل الجبائي، التهرب الضريبي; Digitization, fiscal administration, tax collection, tax evasion